Utilization of Medicinal Plants as Galactagogues to Increase Breast Milk Production as An Effort to Achieve Exclusive Breast Milk in Realizing the Golden Generation of 2045 - Niki Astria; Dwi Rahmawati; Liani Setyarsih (GLOBAL HEALTH SCIENCE GROUP, 2024)
Providing breast milk to babies has a direct impact on the nutritional status and health of children. The various benefits provided by breastfeeding for mothers and children affect the child's immunity, nutrition, body and psychological status. Breastfeeding mothers must pay attention to several things to improve the quality and quantity of their breast milk, one of which is by consuming vegetables as galactogogues which are relatively safe to use. Synthetic galactogogue drugs are known to have side effects if consumed long term. The aim of this research is to determine the benefits of medicinal plants as galactagogues to increase breast milk production as an effort to achieve exclusive breast milk in realizing the Golden Generation 2045. The research method was carried out experimentally using medicinal plants, namely Moringa oleifera leaves, Musa paradisiaca, and Sauropus androgynous L. consisting of 3 groups that were given treatment, while the control group was not given treatment. Data was taken using direct measurements of the amount of breast milk production of respondents in both groups receiving intervention I (Moringa Leaves), Intervention II (Banana Heart), Intervention III (Katuk Leaves) and in the Control group. Then the results The research was analyzed using the Kruskal-Wallis statistical test. The results of the study show that there is a difference in breast milk production in the intervention group and the control group with a p-value of 0.046 (<0.05). Thus, in the future, this research will be able to contribute to optimizing breast milk production as a first step in preventing various health problems, especially stunting and wasting, so that a golden generation can be realized.